Rekonseptualisasi hukum adat kontemporer : telaah kritis terhadap hukum adat sebagai hukum yang hidup dalam masyarakat - Soemadiningrat, H. R. Otje Salman, 1939- (Bandung : Alumni, 2002)
Structure and implementation of adat law in accordance with shared value system of social life of Indonesian people
Includes bibliographical references (p. 221-228).
Keywords: Adat law -- Indonesia; Social values -- Indonesia